A 2-pyridone modified zinc phthalocyanine with three-in-one multiple functions for photodynamic therapy. Issue 25 (25th February 2021) - Li, Yanqing; Wang, Chongchong; Zhou, Lin; Wei, Shaohua
Abstract : A 2-pyridone modified zinc phthalocyanine (denoted ZnPc-PYR) achieves a one stone for three birds outcome in the photodynamic therapy (PDT) treatment of cancer. Abstract : A 2-pyridone modified zinc phthalocyanine (denoted ZnPc-PYR) achieves a one stone for three birds outcome in the photodynamic therapy (PDT) treatment of cancer. ZnPc-PYR can be excited by both 665 and 808 nm light to treat superficial and deep tumors, store and slowly release singlet oxygen ( 1 O2 ) to improve its utilization and downregulate the HIF-1 (hypoxia-inducible factor 1) expression level to enhance the tumor cell's sensitivity to PDT treatment under hypoxic conditions.